Pengaruh Variasi Temperatur Quenching pada Aluminium Paduan AlMgSi-Fe12% terhadap Keausan - Wardoyo Wardoyo; Sumpena Sumpena (Jurnal Engine: Energi, Manufaktur, dan Material, 2018)
The purpose of this research is to determine the effect of heat treatment hardening of AlMgSi-Fe12% casting aluminium alloys on wear. The tests were carried out on specimens of raw materials and heat-treated specimens with variations of temperature used were 550 oC, 575 oC, 600 oC, and 625 oC, and used 15 minutes of holding time in each heat treatment, then quenching in SAE 20 oil. The method used for wear-tested was high speed ogoshi universal testing machine wear. The result had shown on raw material a specific wear rate was 2.256102E-07 mm2/kg. Test results on the specimens that have received heat treatment hardening temperature 550 oC increased the wear value decreased to 1.7471E-07 mm2/kg. In materials with temperature heat treatment, 575 oC causes wear values were increased when compared with raw material, respectively, 2,83739E-07 mm2/kg. In materials with temperature heat treatment 600 oC also causes wear values were increased when compared with raw material, respectively, 2,65105E-07 mm2/kg. Test results on the test material that has received heat treatment temperature 625 oC increased the wear value decreased to 2.16777E-07 mm2/kg.